CULTIVATING ENGLISH PROFICIENCY FOR ENHANCED CUSTOMER SERVICE IN INDONESIAN RAILWAYS: A STUDY ON VOCATIONAL TRAINING NEEDS - Candra, Budi; Khoiriyah, Khoiriyah (English Review: Journal of English Education, 2024)
This research aims to conduct a need analysis of English communication skills learning materials that can better meet the demands of workplace, to be specific for customer service employees in Indonesian Railways Company (PT.KAI). Thirteen employees were purposefully selected as the respondents. Using mixed methods, a survey and in-depth interview were carried out to collect the data. The result showed that almost all of the participants did not always speak English in their day-to-day working time. Yet, they still highly demanded to improve their English communication skills, especially both in listening and speaking skills to improve their professionalism and to meet the workplace requirements. Some topics were highlighted as the learning materials that meet with their needs such as showing empathy, ending conversation, thanking conversation, and other topics related to tourism and giving directions and many more. Thus, this research is expected to give preliminary evidence for the EOP course designers, ESP practitioners, book publisher, or even vocational training center to design more relevant materials.